Assessment of the potentialities of recycled steel fibres for the reinforcement of cement based materials - Barros, Joaquim A. O. (2013)
Recent research is evidencing that adding steel fibres recycled from wasted tires can improve the post-cracking behaviour of cement based materials, enhancing the ductility, energy dissipation and impact resistance of elements made by this type of composites. As a consequence, Recycled Steel Fibre Reinforced Concrete (RSFRC) appears as a promising candidate for both structural and non-structural applications. To contribute for the assessment of the potentialities of RSFRC, an experimental program composed of three series of notched beam bending tests with concrete reinforced with 45, 60 and 90 kg/m3 of recycled steel fibres (RSF) was carried out by determining the post-cracking residual strength parameters, fR,,j, defined according to the recommendations of the CEB-FIP Model Code 2010. Based on the obtained fR,,j, the constitutive laws characterizing these three RSFRC were determined and used to estimate the reinforcement potentialities of RSFRC for structural applications. A data base with fR,,j corresponding to industrial steel fibres (ISF) was built in order to compare the post-cracking performance of RSFRC and concrete reinforced with Industrial steel fibres (ISF). This paper describes the experimental program, and presents and discusses the obtained results.